Assosiation Between Mother Knowledge Related Nutrition and Complementary Feeding Pattern with Nutrition Status of 6 – 24 Months Children - Regina Maria Boro (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2017)
Complementary feeding is the important meal should give to the children 6 – 24 months as a complement of breastfeeding. Mother as a key person who has a responsibility for caring and gives great meal for children. Before mother prepares a great meal for children, they should have good knowledge about nutrition and how to feed their children. The aim of the study is to know associations between mother’s nutrition knowledge and complementary and complementary feeding pattern with nutritional status of the children. This study was a quantitative study with a cross-sectional design and was done in 41 samples mother and child in age 6 – 24 months old by Cluster sampling. Result: Most of the mother knew was in the middle category (48.8%), and nutrition status of the children was 31.7% in mild undernutrition, 9.8 % in severe undernutrition, 24.4% in mild stunting, and 34.1% severe stunting. More than 60% was a good complementary feeding pattern. There was a significant association between mother’s knowledge with complementary feeding pattern as linear as that there was a significant association between complementary feeding patterns with nutritional status. This study was found that a mother’s nutrition knowledge will influence the complementary feeding practice and will influence the nutritional status of the children.